(3JOQjH GdQGhi aj TQM JbQjH GdfhGhis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3Gdfhhj,J (B676 (3g` s ((3NjQ GdOjf Hf eMeO Hf HcJhJ s)
(3ChdgG (B:s
(3CeG HYO , aEf Yde GdMOjK QajY GdbOQ aQCjJ cJGH GdJbQjH hGdJjSjQ dCHi RcQjG GdfhGhi abhi GdYRe Ydi cJGHI TQM Ydjg cGad HEjVGM eYGfjg s
(3BNQgG (B:s
(3hQLGd GdESfGO GdPi SbfGg efi Edi YHO Gddg Hf YeQh cdge eUQjhf , hGddg CYde BNQ TQM GdJbQjH s
(3GdfSNI HgG MhGTs
(3HChdgG JedcGJ efgG eG jYhO Edi SfI (B1021(3g`s
(3cJH GdeJf HGdMeQIs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdMOjK h GdeUWdMs